ANALYSIS OF THE INCIDENCE OF AIDS IN YOUNG PEOPLE IN THE NORTHEAST 2020 to 2022 - Costa Duart, Tamires; de Carvalho Alves, Winícius; Barbosa Resende, Danilo; Sthefanye Urçulino Dorneles, Jéssica; da Silva Viana Paulo da Costa Araújo, Yara; Irwin Flores Souza, Wallace; José Matos da Silva, Gustavo; Vieira Benevides Ferreira, Arthemis (Health and Society, 2023)
Introduction: AIDS is a chronic disease that impairs the immune system and the body’s ability to fight other infections, such as neurotoxoplasmosis, pneumocystis disease and tuberculosis. AIDS stands for Acquired Immunodeficiency Syndrome. AIDS is caused by the HIV virus, which is a sexually transmitted virus, but can also be transmitted by infected blood or vertical transmission. with a view to presenting the epidemiological incidence of AIDS cases in the northeast region of Brazil. Objective: To analyze the incidence of AIDS in young people in the Northeast region, from 2020 to 2022. Methodology: This study was carried out through a cross-sectional analysis, whose purpose was to collect and interpret the data that cover the epidemiological statistics of the incidence of AIDS in young people in the Northeast region, from 2020 to 2022. Data collection took place between June 2022 and September February 2022, using the SUS Hospital Information System (SIH/SUS) and the Unified Health System (DATASUS). Results and Discussion: In view of the evidence found, the findings indicate that, over the years, there has been a decrease in the notification of cases. Thus, in analysis, it was possible to see that compared to the years 2020 to 2022, the decline in AIDS cases was quite significant. Some factors contributed to the decrease in notifications, among them the emergence of the Covid-19 pandemic. In the peak years of the coronavirus, health services were focused on controlling the spread of the virus, thus many other notifiable diseases were neglected, including AIDS. In addition to this, it is highlighted that not all data during this period are reliable. Conclusion: It was noticeable that the notification occurred more frequently among 19-year-olds and the state with the highest notification was Bahia in all the added criteria. Therefore, the objective of this study was achieved, demonstrating the most relevant data on the subject. Therefore, it is proposed that more studies be carried out on the subject.